VD_FINDINFO 31/2011/DCA vom 18. Februar 2011 - VD Tribunal cantonal (2011)
ARRANGEMENT DE MADRID CONCERNANT L'ENREGISTREMENT INTERNATIONAL DES MARQUES, PROTECTION DES MARQUES, REGISTRE DES MARQUES, NOTORIÉTÉ, PRINCIPE DE LA TRANSPARENCESOCIÉTÉ, CLAUSE PÉNALE | 53 CO, 620 al. 2 CO, 109 al. 1 LDIP, 109 al. 2 LDIP, 110 al. 1 LDIP, 112 LDIP, 6 al. 1 LDIP, 74 LOJV, 18 LPM, 3 al. 1 LPM, 55 al. 1 let. a LPM, 55 al. 1 let. b LPM, 55 al. 1 let. c LPM, 58 al. 3 LPM, 404 CPC (CH)